Improving outpatient satisfaction by extending expected waiting time - Wei-Min Ma; Hui Zhang; Neng-Li Wang (BMC, 2019)
Abstract Background Long waiting times result in low satisfaction. Although several methods are used to shorten the actual waiting time (AWT) in large hospitals of China, the outpatients still have a long actual waiting time. This study aimed to explore whether satisfaction could be improved by extending the expected waiting time (EWT) instead of shortening the AWT. Methods In October 2016, 257 students in grade one voluntarily participated in this study. They came from 6 classes, which were randomly divided into two groups: 3 classes comprised the control group (n = 125) and 3 classes comprised the experimental group (n = 132). Unfavorable information (UI) was given to the experimental group alone. Six distinct questionnaires were designed to explore the effects of UI on EWT and the effects of an extended EWT on satisfaction. Satisfaction scores ranged from 0 to 100: 0-25, very dissatisfied; 26-50, dissatisfied; 51-75, satisfied; 76-100, very satisfied. Each participant finished one of the 6 questionnaires online. Of the 257 questionnaires, 233 were valid. Results Before UI was given, the initial EWT (T0) was similar between the control and experimental groups (Z = -1.924, P = 0.054). Under the effects of UI, individuals in the experimental group extended their EWT (T1) from 121.0 to 180.0 min (Z = -6.367, P < 0.001). Females prolonged their EWT longer than males did (Z = -2.239, P = 0.025). Then, this study defined T0 = 1.5 h and T1 = 2.5 h, and compared the satisfaction scores between the control and experimental groups: a significant difference was found when AWT =2.0 h (t = − 3.568, P = 0.001), but not when AWT =3.0 h (t = − 0.718, P = 0.475) or when AWT =1.0 h (t = − 1.088, P = 0.280). When AWT =3.0 h, fewer individuals felt "very dissatisfied" in the experimental group (21.2%) than in the control group (44.7%) (χ 2  = 4.368, P = 0.037). Conclusions EWT was found to be extended greatly by UI. An extended EWT could improve satisfaction scores.